Generalized annular granuloma associated with crowned dens syndrome, which resolved with colchicine treatment. (1st August 2016) - Cozzani, E.; Basso, D.; Cimmino, M. A.; Larosa, M.; Burlando, M.; Rongioletti, F.; Drago, F.; Parodi, A.
Summary: Granuloma annulare (GA) is a chronic, benign, and usually self‐limiting cutaneous inflammatory disease, typically characterized by small, localized, skin‐coloured papules that are usually asymptomatic or mildly pruriginous. Its aetiopathogenesis is still unknown and treatments are rarely effective. Generally, 50–70% of localized GA cases are self‐limiting and show spontaneous resolution after 1–2 years, whereas disseminated GA is less likely to disappear without treatment. Treatment of generalized GA is usually based on single case reports, and only a few studies involving large case series have been published. We present the case of a patient affected by generalized GA, which resolved after colchicine treatment used for concomitant crowned dens syndrome due to calcium pyrophosphate deposition disease (CPPD). Colchicine may have worked by a direct action on GA or, alternatively, by controlling CPPD, as a possible trigger. As the low‐dosage colchicine treatment was well tolerated by our patient, this could be easily used in the management of GA. However, further studies are needed to confirm the action of colchicine on GA.